Physiological Comparison of Pure American and Hybrid American-Chinese Chestnut Hybrids - Sam Cleary (UNC Test Journal, 2024)
The American chestnut (Castanea dentata [Marsh.] Borkh.), once a dominant canopy species in eastern North America, fell victim to invasive pathogens in the early 20th century. The American Chestnut Foundation (TACF) spearheads restoration efforts using backcrossed hybrids with Chinese chestnut (Castanea mollissima Blume) for pathogen resistance. To understand how backcrossed chestnut hybrids (BC1F1 with 75% American genotype and BC3F3 with 94% American genotype) perform compared to pure American chestnut, this study investigated their photosynthetic capabilities and water relations in western North Carolina. Photosynthetic capacity was compared among these three chestnut classes with steady-state light response curves. Dark respiration rates, quantum yield, and maximum photosynthetic rates differed among the three chestnut types, but these did not result in differences in light compensation point, a measure of shade tolerance. In July and August, plant water potential was measured at predawn, morning and afternoon, and leaf gas exchange was assessed in the morning and afternoon under ambient conditions. Blight effects on the 100% stand resulted in small, shrubby plants that differed in size and light environment, so diurnal measurements were only taken in the two hybrid stands. Soil moisture and pre-dawn water potential were generally similar between the two stands, however, there were significant differences in daily gas exchange and water potential, with the 75% American chestnuts generally having higher rates of gas exchange in the afternoon, while also experiencing lower plant water potential and a greater change between pre-dawn and afternoon water potential. These results suggest that the 75% American chestnuts may be better able to perform under moderate atmospherically-induced water stress in the afternoon. Quantifying relationships between water relations, gas exchange, and environmental factors will allow us to evaluate long-term performance and inform robust planting site selection and management practices.